The answer is: The third option, 0.
We are asked to find (f-g) evaluated in 144, so the definition states that:
So,
We must remember that evaluating a function means replacing the variable with the given value, for this case it's 144.
Then, evaluating:
Hence, if:
The correct option is the third option, 0.
Have a nice day!
Answer:
0
Step-by-step explanation:
Substitute x = 144 into the expression for f(x) - g(x)
+ 12 - 2
= 12 + 12 - (2 × 12)
= 12 + 12 - 24
= 0
1. 4y > 20
4y / 4 > 20 / 4
y > 5
2. 7x + 21 < -28
7 < -28 - 21
7x < -49
x < -7
3. -12m - 24 > 36
-12m > 36 + 24
-12m > 60
m < - 5
hope this helped :)
Answer:
(of an algebraic expression) consisting of three terms.
Example:
3x2 − 3y2 + 2
Answer:
x = 2
Step-by-step explanation:
2x = 4
x = 2
Answer: X = 2
Step-by-step explanation:
so first you find out what 2x equals to which is
2x = 4
then you solve for x and the answer is 2
x = 2
Answer:
-3
Step-by-step explanation:
-x^2 +x–1
Let x = -1
- (-1)^2 + (-1) -1
- 1 -1 -1
-3
Answer:
0
Step-by-step explanation:
the equation after plugging in "x" is
-(-1)*(2)+(-1)-1
then after multiplication it is
2-1-1
this becomes 0